2016
DOI: 10.1016/j.celrep.2016.05.082
|View full text |Cite
|
Sign up to set email alerts
|

The TIP60 Complex Is a Conserved Coactivator of HIF1A

Abstract: SUMMARY Hypoxia inducible factors (HIFs) are critical regulators of the cellular response to hypoxia. Despite their established roles in normal physiology and numerous pathologies, the molecular mechanisms by which they control gene expression remain poorly understood. We report here a conserved role for the TIP60 complex as a HIF1 transcriptional cofactor in Drosophila and human cells. TIP60 (KAT5) is required for HIF1-dependent gene expression in fly cells and embryos, and colorectal cancer cells. HIF1A inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 49 publications
2
91
0
Order By: Relevance
“…In fact, in certain contexts CDK8 has been described as a tumor suppressor (Clark et al, 2015; Gu et al, 2013; Li et al, 2014). We and others have shown that CDK8 is a positive regulator of transcriptional programs that drive the proliferation and survival of cancer cells, including those controlled by Wnt/β-catenin (Firestein et al, 2008), ERK/MAP kinase signaling (Donner et al, 2010), and HIF1A (Galbraith et al, 2013; Perez-Perri et al, 2016). Thus, it is possible that pharmacological inhibition of CDK8 could have therapeutic value by simultaneously decreasing the activity of multiple oncogenic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in certain contexts CDK8 has been described as a tumor suppressor (Clark et al, 2015; Gu et al, 2013; Li et al, 2014). We and others have shown that CDK8 is a positive regulator of transcriptional programs that drive the proliferation and survival of cancer cells, including those controlled by Wnt/β-catenin (Firestein et al, 2008), ERK/MAP kinase signaling (Donner et al, 2010), and HIF1A (Galbraith et al, 2013; Perez-Perri et al, 2016). Thus, it is possible that pharmacological inhibition of CDK8 could have therapeutic value by simultaneously decreasing the activity of multiple oncogenic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the histone acetyltransferase TIP60 was recently reported to enhance HIF-1 transcriptional activity and activate about 25% of HIF-1 downstream target genes in colorectal cancer HCT116 cells [30]. TIP60 is recruited by HIF-1α to the hypoxia response element of the HIF-1 target gene ANKRD37 .…”
Section: Regulation Of Hif Transcriptional Activity By Epigenetic Wrimentioning
confidence: 99%
“…In addition, the TIP60 complex is required for HIF1-dependent gene expression in fly cells and embryos, as well as colorectal cancer cells. TIP60 is recruited by HIF1 to chromatin during hypoxia and functions as a coactivator of HIF1 action by recruiting RNA-Polymerase II onto chromatin [186]. Finally, Musashi (Msi, dMsi in Drosophila) represses sima mRNA translation by binding an Msi-binding element within the 3′ UTR of the sima transcript.…”
Section: Upstream Regulators Of Hif-1α/sima In Hypoxiamentioning
confidence: 99%
“…Further work on Sima regulators has uncovered several modifiers of Sima function in hypoxia in Drosophila, such as the microRNA miR-190, the TIP60 chromatin remodeling complex and the RNA-binding protein Musashi [184][185][186] (Figure 2). miR-190 acts as a positive regulator of the hypoxic response by targeting directly the propyl-4-hydroxylase Fga, which is the principal negative regulator of Sima.…”
Section: Upstream Regulators Of Hif-1α/sima In Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation